WORKSHOP PENGENALAN KOMPETENSI INSTALASI PEMBANGKIT LISTRIK TENAGA SURYA - Utami, Sri; Mardiyanto, Ignatius Riyadi; Mursid, Sri Paryanto; Mursanto, Wahyu Budi; Rahardjo, Agoeng Harjatmo; Widarti, Sri; Pudin, Apip (Universitas Djuanda, 2022)
The use of abundant solar energy in Indonesia is a concern for the government, especially for areas that are still not electrified by the PLN cable network. The conversion of solar energy to electrical energy is carried out using PV solar panels to form a solar power plant (PLTS). The existence of this PLTS is increasing throughout Indonesia so that it takes human resources who have these competencies to manage it. With this awareness, the Community Service Activity (PKM) program of the Department of Energy Conversion Engineering at the Bandung State Polytechnic invites a partner at SMKN 1 Cimahi to jointly equip its students to get a PLTS competency briefing. One of the competencies developed is about the installation of the solar power plant electrical system. This activity was held during the very dangerous Covid-19 virus pandemic which forced people to work at home (WFH). However, instead of being an obstacle, it provides an appreciable result, namely the gain of experience to develop learning modules that can be delivered online. The analysis of the results of the PKM implementation proved that one way of providing knowledge on the aspect of knowledge can be held online.